2014
DOI: 10.1111/sji.12198
|View full text |Cite
|
Sign up to set email alerts
|

Naive Tumour‐Specific CD4+ T Cells were Efficiently Primed in Acute Lymphoblastic Leukaemia

Abstract: 1 Authors contributed equally to this work. AbstractThe recognition and neutralization of tumour cells is one of the big challenges in immunity. The immune system has to recognize syngeneic tumour cells and has to be primed and respond in an adequate manner. Priming of a leukaemiaspecific immune response is a crucial step in tumour immunology that can mislead to tumour tolerance either by T cell ignorance, deletion or Treg induction. To resemble the situation of acute lymphoblastic leukaemia (ALL) in patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, a number of studies have indicated that CD4 + T cells contribute to the eradication of tumors even in the absence of CD8 + T cells ( 41 , 42 ). Cytotoxic CD4 + T cells have been shown to be capable of directly eliminating tumor cells that are MHC class II positive, in addition to indirectly killing tumor cells that lack MHC class II expression ( 43 , 44 ). In the present study, it was found that the systemic injection of rat-derived β-EP, a homogenous opioid peptide, increased CD3 + , CD4 + and CD8 + T cell subtype expression in a rat model of bone cancer pain, while the systemic injection of morphine, a heterogenous opioid compound, reduced their expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have indicated that CD4 + T cells contribute to the eradication of tumors even in the absence of CD8 + T cells ( 41 , 42 ). Cytotoxic CD4 + T cells have been shown to be capable of directly eliminating tumor cells that are MHC class II positive, in addition to indirectly killing tumor cells that lack MHC class II expression ( 43 , 44 ). In the present study, it was found that the systemic injection of rat-derived β-EP, a homogenous opioid peptide, increased CD3 + , CD4 + and CD8 + T cell subtype expression in a rat model of bone cancer pain, while the systemic injection of morphine, a heterogenous opioid compound, reduced their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the interaction between EPHB4 and ephrin-B2 is involved in the inhibition of T-cell proliferation by activating the Src, phosphoinositide 3-kinase (PI3K), Abelson murine leukemia (Abl) and N-terminal kinase signaling pathways ( 19 ). It has also been suggested that T cells are important in mediating antitumor immune responses; therefore, insufficient priming of CD4+ T cells may result in impaired specific anti-leukemia immunity and subsequently enhance the invasive ability of leukemic cells ( 20 , 21 ). The role of EPHB4 in the modulation of T-cell physiology implies that EPHB4 gene methylation may be associated with ALL pathogenesis ( 22 ).…”
Section: Introductionmentioning
confidence: 99%